PEMANFAATAN PLATFORM IPUSNAS DALAM MENINGKATKAN LITERASI DIGITAL MAHASISWA INSTITUT AGAMA HINDU NEGERI GDE PUDJA MATARAM - Dirga, I Ketut; Wiguna, Ida Bagus Alit Arta (Lembaga Penerbit Sekolah Tinggi Hindu Dharma Klaten, 2025)
This study aims to explore the utilization of the iPusnas platform in enhancing the digital literacy of students at the State Hindu Institute of Gde Pudja Mataram. iPusnas, as Indonesia’s national digital library, provides free and easy access to thousands of electronic books relevant to academic needs. This research adopts a qualitative approach using non-participant observation, structured interviews, and document analysis involving students who actively use iPusnas. The findings show that students use iPusnas primarily to search for references for assignments, write papers, and complete their theses. The most frequently used features are the search function and the digital book collection. However, several challenges were identified, including limited book availability, unstable internet connections, and a lack of understanding in using advanced features. Furthermore, the absence of proper training has led to suboptimal digital reference management among some students. Therefore, it is essential for the institution to provide outreach and training on the effective use of iPusnas. Improved utilization of iPusnas not only allows students to access academic resources more efficiently but also enhances their digital literacy skills, which are increasingly vital in today’s technological era.